Analisis Penjejak Lintasan Mobile Robot dengan Pengendali Gerak Menggunakan Bluetooth - Zulkarnain Zulkarnain; Ismail Thamrin; Astuti Astuti; Marwani Marwani; Ellyanie Ellyanie; Dimas Prayoga Pamungkas (Jurnal Rekayasa Mesin, 2021)
This research was carried out aiming to see the temperature around the occurrence of natural disasters using temperature and humidity sensors that were used as robot eyes, and bluetooth sensors were used to control the robot car by connecting with android as a controller. The benefit of this research is to make it easier for the SAR team to search for victims of natural disasters and make time more efficient and reduce the risk of accidents for the SAR team. The research method used is qualitative with testing documentation techniques carried out and recording the data obtained. From the results of this study, it was found that the sensor used can see the ambient temperature and humidity and the bluetooth sensor control distance reaches 140 meters.